EEG Signal Analyzing and Simulation Under Computerized Technological Support - V, Rohith; T.V, Prajitha; Suresh, Sweety (International Journal of Engineering and Technology, 2018)
Electroencephalogram (EEG) is a method for acquiring the brain signals for diagnostic purposes. It tracks and records the brain wave patterns. This is a non-invasive technique. The idea behind is to categorize the EEG signal based on the frequency range. The steps include collecting EEG signals, pre-processing, feature extraction, feature selection and classification. The pre-processing eliminates the noises from the signal. EEG signal can be disintegrated by using discrete wavelet transform. The feature extraction methods are used to obtain the time-domain features of the EEG signal. Finally, the classification method determines the variations in the mental state of the person.Â Â